Mussolini and fascist Italy - Blinkhorn, Martin, 1941- (New York, N.Y. ; London : Routledge, 1991)
'Mussolini and Fascist Italy' explains the significance of the man, the movement and the regime which dominated Italian life between 1922 and the Second World War.
1. Introduction -- 2. The setting: liberal Italy, 1861-1915 -- 3. The seedbed of Fascism -- 4. The conquest of power, 1919-25 -- 5. Italy under Fascism -- 6. Diplomacy and imperialism, 1922-36 -- 7. The decline and fall of Fascism, 1936-45 -- 8. Interpreting Italian Fascism -- Conclusion.
The Roger Griffin ComFas Collection
Keywords: Mussolini, Benito, -- 1883-1945.; Fascism -- Italy -- History -- 20th century; Italy -- Politics and government -- 1922-1945.